INDONESIA'S SOFT POWER STRATEGY IN GUIDING PEACE IN THE AFGHANISTAN CONFLICT - Arief Rachman; Muhtadi Muhtadi; Kiki Al Hadid (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
The commitment of the Government of Indonesia in carrying out soft power can build the image of Indonesia as a bridge country for peace in the eyes of the international community. It can also build international trust for the national interest. Afghanistan is one of the countries that has been hit by a protracted conflict due to differences in political ideology and interference from other interested countries. This research aims to analyze Indonesia's soft power role and strategy in guiding various meetings with related parties in the context of peace in Afghanistan. The research method used in this research is the qualitative research method, with a naturalistic approach to accurate analysis of the material and strategy of Indonesian soft power in guiding peace in Afghanistan. The results obtained in this research are about matters relating to Indonesia's Soft Power Strategy in guiding peace in Afghanistan in the form of guiding various organizations and stakeholders that play a role in peace in Afghanistan, both Afghan government organizations, party leaders in Afghanistan, US Embassy Special Charge d'Affaires Ambassador, High Council for National Reconciliation (HCNR) Afghanistan, National Security Adviser (NSA) Afghanistan and Council of Afghan Scholars and other organizations that play an active role in peace in Afghanistan. Keywords: Soft Power Strategy, Peace Guidance, Indonesia and Afghanistan